Interactive Effect of Blackeye cowpea mosaic virus and Cucumber mosaic virus on Vigna unguiculata - Ayodele Anthony Fajinmi (Horticultural Plant Journal, 2019)
This research tries to demonstrate physiological effect of combined infection of two viruses on growth parameter of cowpea plant as demonstrated through symptom expression. Blackeye cowpea mosaic virus (BlCMV) and Cucumber mosaic virus (CMV) were transmitted to cowpea plants by mechanical rub inoculation. This study showed that the differences in stem height and final aboveground fresh weight of cowpea plants inoculated with mixed infection with CMV and BlCMV were significantly less than those of plants inoculated with a single virus. Likewise cowpea plants inoculated with either virus alone or with CMV and BlCMV mixed infection had less stem height and aboveground fresh weight than the control. The mixed infection of BlCMV and CMV caused significant increase in the severity of symptoms in cowpea and also in the height using factors analysis and Abbott's equation. Symptom severity rating scale used, demonstrated statistical proof for physiological effect based on symptom severity for co-infection. A three phase disease symptom severity expression revealed disease severity for each viral treatment associated with host plant. Keywords: cowpea, virus mixed infection, interaction, severity, symptom